Recent graduates and labour market competencies – Issues of horizontal matching - Márton, Sandor; Fónai, Mihály (Central European Journal of Educational Research, 2026)
This study examines the differences between the competencies possessed by recent graduates and those required in their jobs, with particular attention to horizontal matching. Its theoretical framework integrates human capital theory, job matching models, the skill mismatch approach, and competence theories, highlighting the growing importance of transversal and non-cognitive skills. The analysis is based on the Hungarian dataset of the Eurograduate 2022 survey (N = 6,797) and compares possessed and required competencies based on graduates’ subjective self-assessments, while also examining the degree of horizontal mismatch. According to the results, in most of the examined competencies, only moderate differences can be observed between the required and actual levels, and in several cases, recent graduates rate their own competencies higher than those required for their work. Prominent differences can be observed in some dimensions of digital and communication competencies. Horizontal matching is high, although significant differences are observed by level and field of education. The findings suggest that both the level and the type of competencies play a decisive role in labour market matching, while mismatch is more of a differentiated rather than a general phenomenon.